2021
DOI: 10.3389/fgene.2021.643935
|View full text |Cite
|
Sign up to set email alerts
|

Gene Signature Associated With Bromodomain Genes Predicts the Prognosis of Kidney Renal Clear Cell Carcinoma

Abstract: Bromodomain (BRD) proteins exhibit a variety of activities, such as histone modification, transcription factor recruitment, chromatin remodeling, and mediator or enhancer complex assembly, that affect transcription initiation and elongation. These proteins also participate in epigenetic regulation. Although specific epigenetic regulation plays an important role in the occurrence and development of cancer, the characteristics of the BRD family in renal clear cell carcinoma (KIRC) have not been determined. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In melanoma, the iBRD9 (TP-472) blocked tumor growth by suppressing ECM-mediated oncogenic signaling and inducing apoptosis [ 34 ]. In renal clear cell carcinoma, the combined analysis of BRD9 and other chromatin regulated genes showed a significant association with the high-risk groups and lower overall survival, providing a survival prediction model for further research investigating the role of the expression of BRD genes in cancers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In melanoma, the iBRD9 (TP-472) blocked tumor growth by suppressing ECM-mediated oncogenic signaling and inducing apoptosis [ 34 ]. In renal clear cell carcinoma, the combined analysis of BRD9 and other chromatin regulated genes showed a significant association with the high-risk groups and lower overall survival, providing a survival prediction model for further research investigating the role of the expression of BRD genes in cancers [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, brd8b was the highest expressed gene in the tilapia liver, indicating its possible role in liver development. Brpf3 was shown to be critical in renal clear cell carcinoma (KIRC) [ 59 ]. Interestingly, brpf3b was the most highly expressed gene in the tilapia kidney, suggesting it may affect kidney development.…”
Section: Discussionmentioning
confidence: 99%
“…SIN3A, as a chromatin-remodeling gene, was reported to be associated with regulating YY1, which would result in the degradation of oncoproteins of ccRCC [41]. EP300, associated with six other bromodomain genes (KAT2B, KAT2A, BRD9, SP140, SMARCA2, BRPF3) based signature could predict ccRCC patients' prognosis [42]. As for BPTF, Zhang et al revealed the roles of the METTL14/BPTF axis in the metabolic remodeling and epigenetics of metastatic RCC [43].…”
Section: Discussionmentioning
confidence: 99%